The Art of Participation : 1950 to now. - Atkins, Robert; Frieling, Rudolf; Groys, Boris; Manovich, Lev (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2008)
Abramovic, Marina & Ulay ; Acconci, Vito ; Alys, Francis ; Baldessari, John ; Beuys, Joseph ; Blank & Jeron ; Gohlke, Gerrit ; Brecht, George ; Brucker-Cohen, Jonah ; Bennett, Mick ; Cage, John ; Cardiff, Janet ; Clark, Lygia ; Cuevas, Minerva ; Eichhorn, Maria ; Export, Valie ; Fletcher, Harrell ; Rubin, Jon ; Fluxus ; Galloway, Kit ; Rabinowitz, Sherrie ; Gerz, Jochen ; Gommel, Matthias ; Gonzalez-Torres, Felix ; Graham, Dan ; Haacke, Hans ; Hershman Leeson, Lynn ; Kaprow, Allan ; Lohner, Henning ; Lord, Chip ; Schreier, Curtis ; Tomb, Bruce ; Lozano-Hemmer, Rafael ; Marioni, Tom ; MTAA (M. River & T.Whid Art Associates) ; Muntadas, Antoni ; Ono, Yoko ; Paik, Nam June ; Phiffer, Dan ; Zer-Aviv, Mushon ; Raqs Media Collective ; Rauschenberg, Robert ; Sack, Warren ; Shiomi, Mieko (Chieko) ; Torolab ; Vostell, Wolf ; Warhol, Andy ; Willats, Stephen ; Wurm, Erwin
The Art of Participation : 1950 to Now, SFMOMA (San Francisco Museum of Modern Art), San Francisco, 2008-11-08. 2009-02-08
boek